Control Interno de la Gestión Administrativa y su Impacto en la Importadora Adrián Cia. Ltda. Del Cantón la Maná Provincia de Cotopaxi. - Cárdenas Icasa, Gilson Orlando (2019)
The field research, previously planned and executed for the development of this information, allowed determining the administrative staff and employees of the entity, who have knowledge of internal control but are not updated according to law, to make a current diagnosis in the importer Adrián Cía. Ltda. It was necessary to make preliminary visits to the facilities, its purpose was to obtain a general knowledge of the entity. For this reason, it was established as a general objective: to evaluate the Internal Control of the administrative management and its impact on the Adrián Cía. Ltda. Importer of La Manà province of Cotopaxi. In the first chapter of the research developed through a non-experimental methodological design that allowed to collect the necessary data, we used methods and instruments such as surveys and interviews that involved the administrative management. The third chapter as a final result it is concluded that the correct use and application of Internal Control design for the management managed based on the COSO I that provides information, in a clear, simple way, about the control procedures and policies that should be applied in the administrative process. Improvements are recommended for the administrative management of the institution.